A Thematic Analysis of Multiple Pathways Between Nature Engagement Activities and Well-Being - Iqbal, Anam; Mansell, Warren (Frontiers in Psychology, 2021)
Research studies have identified various different mechanisms in the effects of nature engagement on well-being and mental health. However, rarely are multiple pathways examined in the same study and little use has been made of first-hand, experiential accounts through interviews. Therefore, a semi-structured interview was conducted with seven female students who identified the role of nature engagement in their well-being and mental health. After applying thematic analysis, 11 themes were extracted from the data set, which were: “enjoying the different sensory input,” “calm nature facilitates a calm mood,” “enhancing decision making and forming action plans,” “enhancing efficiency and productivity,” “alleviating pressure from society's expectations regarding education,” “formation of community relations,” “nature puts things into perspective,” “liking the contrast from the urban environment,” “feel freedom,” “coping mechanism,” and “anxious if prevented or restricted.” The results indicate complementary mechanisms for how nature-related activities benefit mental health and well-being that may occupy different levels of experience within a hierarchical framework informed by perceptual control theory.